Neoadjuvant rectal score is prognostic for survival: A population‐based propensity‐matched analysis. Issue 7 (2nd August 2022) - Naffouje, Samer A.; Manguso, Nicholas; Imanirad, Iman; Sahin, Ibrahim H.; Xie, Hao; Hoffe, Sarah; Frakes, Jessica; Sanchez, Julian; Dessureault, Sophie; Felder, Seth
Abstract: Introduction: Neoadjuvant rectal (NAR) score may serve as a surrogate short‐term endpoint for overall survival (OS) in clinical trials. This study aims to test the NAR score using a large, national cancer registry. Methods: National Cancer Database patients with clinical stage II/III rectal adenocarcinoma (RAC) treated with neoadjuvant chemoradiation (CRT) followed by surgery were selected and divided into low‐, intermediate‐, and high‐NAR subgroups. OS outcomes were analyzed using Kaplan–Meier and logistic regression models. Results: A total of 12 452 patients were selected, of which 5071 (40.7%) were in clinical stage II and 7381 (59.3%) were in clinical stage III; 15.2% had pathologic complete response. The mean NAR score was 10.01 ± 10.61. Six thousand nine hundred and forty‐one (55.7%) did not receive adjuvant chemotherapy (AC) and were propensity‐matched across NAR subgroups (966 in each group). A significant difference in 5‐year OS between low‐, intermediate‐, and high‐NAR groups was observed (85% vs. 76% vs. 68%; p < 0.001). Five thousand five hundred and eleven (44.3%) received AC and 1045 triplets were propensity‐matched per NAR groups. A significant difference was again observed for 5‐year OS (93% vs. 88% vs. 75%; p < 0.001). Logistic regression confirmed NAR strata as a significant predictor of 5‐year OS. Conclusion: NAR score, as a neoadjuvant response measure, is a strong predictor of 5‐year OS, regardless of AC receipt in a heterogenous population of locally advanced RAC patients.